PSYCHOLINGUISTIC ASPECTS OF GRAMMAR: EXPLORING THE INTERFACE BETWEEN LANGUAGE AND MIND (Journal of Science-Innovative Research in Uzbekistan, 2024)
This paper explores the psycholinguistic dimensions of grammar, investigating the ways in which cognitive processes impact the comprehension and application of grammar. It covers important theories, phases of development, how age and skill levels affect learning grammar, and how grammar processing is supported by the brain. The practical consequences for teaching languages are also discussed, emphasizing how crucial it is to match instructional strategies with cognitive concepts